2022
DOI: 10.1155/2022/6852661
|View full text |Cite
|
Sign up to set email alerts
|

MSC-Derived Extracellular Vesicles Activate Mitophagy to Alleviate Renal Ischemia/Reperfusion Injury via the miR-223-3p/NLRP3 Axis

Abstract: Background. MSC-derived extracellular vehicles (EVs) exhibit a protective functional role in renal ischemia/reperfusion injury (RIRI). Recent studies have revealed that mitophagy could be a potential target process in the treatment of RIRI. However, whether MSC-derived EVs are involved in the regulation of mitophagy in RIRI remains largely unknown to date. Methods. RIRI model was established in vivo in mice by subjecting them to renal ischemia/reperfusion. TCMK-1 cells were subjected to hypoxia/reoxygenation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Most studies on miR-223-3p have focused on acute kidney injury and chronic kidney disease, and few studies have investigated miR-223-3p for the treatment of HBV-GN. However, in previous studies, miR-223-3p demonstrated an amelioration of renal ischemia/reperfusion-induced injury ( Yuan et al, 2017 ; Sun et al, 2022 ) and HBx induced downregulation of miR-223 levels ( Yu et al, 2016 ), which was speculated that it might play a protective role in the development of HBV-GN. In this current study, we employed miR-223-3p-deficient BMSC-Exo to validate the renoprotective role of miR-223-3p in restraining ferroptotic damage in podocytes of HBx transgenic mice.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies on miR-223-3p have focused on acute kidney injury and chronic kidney disease, and few studies have investigated miR-223-3p for the treatment of HBV-GN. However, in previous studies, miR-223-3p demonstrated an amelioration of renal ischemia/reperfusion-induced injury ( Yuan et al, 2017 ; Sun et al, 2022 ) and HBx induced downregulation of miR-223 levels ( Yu et al, 2016 ), which was speculated that it might play a protective role in the development of HBV-GN. In this current study, we employed miR-223-3p-deficient BMSC-Exo to validate the renoprotective role of miR-223-3p in restraining ferroptotic damage in podocytes of HBx transgenic mice.…”
Section: Discussionmentioning
confidence: 96%
“…In this regard, miR- 223, miR-23a, miRNA-15b, and miR374a have been previously shown to be correlated with liver fibrosis, regulating lipid and cholesterol homeostasis (69, 7678). Furthermore, miRNA-15b has been reported to regulate ATP levels and mitochondrial ROS production (79, 80), while miR223-3p increases mitophagy in cells with dysfunctional mitochondria (81). Interestingly, serum levels of miR-15b, miR-23a, miR-374a, and let-7a have been recently reported to have great potential as diagnostic biomarkers of nonalcoholic liver fibrosis (82).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mitophagy, overexpression of BNIP3 is sufficient to overcome kidney IR injury [ 44 , 80 ]. Mesenchymal stem cell-derived extracellular vesicles containing miR-223-3p can activate mitophagy and improve kidney IR injury by inhibiting NLRP3 [ 81 ]. Collectively, these findings highlight the potential of mitophagy as a viable target for the treatment of IR injury.…”
Section: Therapeutic Strategies Of Kidney Ischemia-reperfusion Injury...mentioning
confidence: 99%